Comparative Analysis of the Success of the Islamic Economy A Historical Study of the Economic Reforms of Abdul Malik bin Marwan and Umar Bin Abdul Aziz - Muhammad Hafiz Ikhsan; Imsar Imsar; Muhammad Syahbudi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This research aims to analyze the success of the Islamic economy during the leadership of Abdul Malik bin Marwan with Umar Bin Abdul Aziz which was able to increase economic productivity with concepts built from Islamic teachings in creating the welfare of the people. Research uses methodscomparative studies, namely research by comparing two or more variables, to get answers or facts about whether there is a comparison or not of the object being researched, which systematically examines the thoughts and ideas of Abdul Malik Bin Marwan and Umar bin Abdul Aziz. From the research results, it is known that Abdul Malik Bin Marwan had his own way of developing his leadership with a regional expansion system to develop the country's economy and Umar bin Abdul Aziz carried out economic policy reforms with the concept of radd al-mazhalim where he eliminated all injustices including in the fields of trade, agriculture, and sources of state revenue that have an impact on improving the economy.